Analisis Penggunaan Bahasa Gaul Sebagai Ragam Nonformal Pada Dialog Film “Keluarga Besar” - Nazmi, Alya; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (eScience Humanity Journal, 2025)
This study aims to analyze the use of slang as a non-formal language variety in the dialogue of the film “Big Family”. The focus of the study includes the forms of slang, their functions, and the factors influencing their use. The method used was descriptive qualitative, using listening and note-taking techniques for film dialogue containing slang. The results showed nine types of slang, consisting of slang, abbreviations, and foreign language borrowings. Slang is the most dominant form used in the film's dialogue. The use of slang serves to create a relaxed and friendly communication atmosphere, express the speaker's emotions, mark the social identity of the group, and streamline speech. Factors influencing the use of slang include the informal communication situation, the age and social background of the characters, the influence of media and globalization, and the purpose of the communication. Thus, the dialogue in the film “Big Family” represents the use of slang that reflects the linguistic reality of modern society.